Complete mitochondrial genome of Scaphiodonichthys acanthopterus (Cypriniformes, Cyprinidae). (April 2013) - Yang, Jin-Quan; Cheng, Hui-Ling; Wu, Chien-Yu; Tsai, Kun-Chan; Chiang, Hsin-Chieh; Weng, Chen-Wei; Lin, Hung-Du
<x xml:space="preserve">Abstract</x> In this study, we sequenced the complete mitochondrial genome of Scaphiodonichthys acanthopterus (Cypriniformes, Cyprinidae). This mitochondrial genome, consisting of 16, 612 base pairs (bp), encoded genes for 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNAs, and one non-coding control region as those found in other vertebrates, with the gene order identical to that of typical vertebrates. The control region, of 941 bp in length, is located between tRNAPro and tRNAPhe. The overall base composition of the heavy strand shows T 25.23%, C 26.85%, A 31.96%, and G 15.95%, with a slight AT bias of 57.19%.